Upaya Meningkatkan Keterampilan Kolaborasi dan Prestasi Belajar Matematika pada Materi Pecahan Menggunakan Model Problem Based Learning Berbantu Media Konkret Kelas V SD Negeri 2 Sangkanayu - Setiana, Titin; Muslim, Arifin (AS-SABIQUN, 2024)
The objective of this study is to improve the collaboration skills of fifth-grade students and mathematics learning achievement in the fraction topic at SD Negeri 2 Sangkanayu by utilizing the problem-based learning (PBL) paradigm with concrete media. This study used a two-cycle method for classroom action research (CAR). Eachcycle consisted of four steps: planning, implementation, assessment, and reflection. Nineteen students from thefifth grade of SD Negeri 2 Sangkanayu became the research subjects. Tests with assessment questions and non-test surveys about collaboration skills are examples of data instrument strategies. The research findings indicate that students' ability to collaborate with others and perform academically has improved. The average learning outcome in cycle I was 60.65 with a learning completion rate of 65.7%, while the learning achievement results in cycle II obtained an average of 83.68 with a learning completion rate of 86.8%. The average percentage of collaboration skills increased 5.1% from 75.85% in cycle I to 81% in cycle II.